Screening of Active Compounds and LC50 Toxicity Assay of Sunda Porcupine’s (Hystrix javanica F. Cuvier 1823) Quills Crude Extract - Budiman, Muhamad Arif; Ferdian, Pamungkas Rizki; Handayani, Tri Hadi; Nugroho, Herjuno Ari; Elfirta, Rizki Rabeca; Farida, Wartika Rosa (BRIN, 2021)
Sunda porcupine (Hystrix javanica F. Cuvier 1823) is an endemic fauna from Indonesia that its quills are believed to have medical benefits by local people in some regions of Indonesia. However, the benefits have never been well recorded nor proven scientifically. Local people believe the Sunda porcupine’s quills have efficacy to relieve property for treating toothache. There is limited research on Sunda porcupine’s quills, especially the active compounds, which may affect toothache. This research aims to perform basic pharmacological experiments on Sunda porcupine’s quill samples, which includes screening for the active compounds and determining the LC50 toxicity using brine shrimp lethality test (BSLT) method. Sunda porcupine’s quills were first prepared into simplicia powder (60 mesh in size) and then extracted with 70% ethanol by maceration to produce crude extract. We found that the crude extract of Sunda porcupine’s quills contains some active compounds, including alkaloids, flavonoids, saponins, triterpenoids, steroids, and peptides. The LC50 value of the crude extract was 2,683.19 ppm; thus, categorized as non-toxic. These findings can be used to identify the active compounds in Sunda porcupine’s quills and can be used as a background for further research.